Numerical model validation of complex flexible structures for wave energy (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The wave energy sector faces significant challenges related to load reduction and power optimization. These challenges arise from the need to design WECs that can perform efficiently under varying sea conditions. High-energy sea states, though rare, drives the WEC structures design, while lower-energy sea states provide the base line energy production. To address this, morphing machines—systems capable of adapting their structure based on the upcoming wave conditions—are being explored as a promising solution.However, designing machines with adaptable structures introduces significant complexity. While structures that can change are not new, their application in wave energy has generally led to more complex and less reliable systems due to the mechanical intricacies required. Flexible structures have gained traction, flexible wind turbine blades are an obvious example but flexible robots are a more recent case. These structures are both cost-effective and functional, representing a promising avenue for WEC design. Their flexibility could allow for adaptive performance without increasing mechanical complexity. The complex nature of wave-structure interactions  and the structural deformation makes the modeling of such systems challenging. Accurate modeling involves not only the hydrodynamic forces resulting from wave interactions, but also a coupling with FEM structural deformation models: high-fidelity numerical models are the common choice, but require careful validation and the computational cost is substantial.The objective of this work is to estimate the uncertainties associated with a simplified numerical model of a WEC that incorporates a multibody flexible structure with BEM models.The key approach to estimating these modeling uncertainties involves comparing the results from the numerical model with experimental data. This comparison is made for both operational and extreme load conditions, which are crucial for understanding how the system behaves across the spectrum of real-world wave scenarios. By validating the linearized numerical model with experimental data, the work aims to confirm the hypothesis that flexible structures can indeed reduce the cost of energy for wave energy converters. This would be achieved by optimizing power absorption during frequent, low-energy sea states while maintaining the structural integrity and durability of the WEC under extreme conditions.The process of uncertainty estimation focuses on how well the numerical model can predict the actual performance and behavior of the flexible WEC structure under various wave conditions. The primary goal is to determine the confidence in the model’s predictions and understand where potential discrepancies between the model and reality may arise. This involves:• Experimental data comparison: Using data from wave tank experiments or field tests to compare against the predictions from the linearized numerical model.• Sensitivity analysis: Evaluating how changes in the input parameters affect the system's performance, which helps to identify the most critical factors influencing the WEC’s behavior and power generation.The findings will help inform design decisions and promote the use of flexible structures in wave energy, which may offer significant advantages in terms of cost-effectiveness and adaptability under varying sea conditions.